What Boosts Talent Development? Examining Predictors of Academic Growth in Secondary School Among Academically Advanced Youth Across 21 Years. (October 2019) - Wai, Jonathan; Allen, Jeff
We examined 482, 418 students who took the ACT in the seventh grade and again in high school, taking an exploratory analytic approach to examine academic growth trends from 1996 to 2017. Predictors included sociodemographics, interests, high school (HS) characteristics, HS coursework and GPA, and extracurriculars, which explained 25% of the variance in academic growth. Overall, growth improved from 2005 to 2017, but growth for low-income and Hispanic students was stagnant. Catholic and private school students had the highest growth; homeschooled and high-poverty public school students had the lowest. High growth was associated with STEM (science, technology, engineering, mathematics) elective HS courses and advanced AP, accelerated, and honors courses. Students with investigative and conventional interests had higher growth. Some extracurriculars had significant relationships with academic growth, though the effects were small.